Contemporary issues in international law : a collection of the Josephine Onoh memorial lectures - Freestone, David; Subedi, Surya P., 1958-; Davidson, Scott, 1954- (Kluwer Law International, 2002)
This book contains a collection of the annual Josephine Onoh Memorial Lectures, which are hosted by the University of Hull. The subjects they address include trends in international law, international law and revolution, the European Convention of Human Rights and European Community law concepts.